RELATIONSHIP CONCENTRATION NITRATE, PHOSPHATE AND SILICATE WITH ABUNDANCE OF PLANKTONIC DIATOM IN THE WATERS OF PANGKALAN SESAI VILLAGE,DUMAI ,RIAU PROVINCE - Putri, Zulherija; Nurrachmi, Irvina; Elizal, Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Diatom is the most primary producer in marine waters and is abundant in surface areas that have sufficient light intensity and are rich in nutrients. This research was held on 12-24 May 2018 in the waters of Pangkalan Sesai village, Riau province. The study aims to analyze the concentration of nitrates, phosphate, silicate and analyze the abundance of planktonic diatoms as well as see the relationship of nitrate, phosphate and silicate against diatomic abundance of planktonic. The method used in this research is a survey method that is to perform observations and sampling directly, then proceed with the identification of planktonic diatoms samples in the laboratory. Water quality measurements are done in situ and ex situ consisting of parameters, physical biology, and chemistry. The concentration of nitrate ranged from 0.0367 – 0.0506 mg/l, phosphate concentrations ranged from 0.0840 – 0.1397 mg/l and silicate concentration of 0.0502 – 0.0692 mg/L. Diatom planktonic was found in the waters of Pangkalan Sesai village as many as 9 (nine) genera. Based on the results of multiple linear regression analyses obtained the value of the physical correlation (R) with the value 0.667 indicates that the relationship between nitric concentration, phosphate and silicate in diatoms is moderate. Then the value of R Square (R2) is worth 0.444 meaning the percentage of donations from the variable nitrate, phosphate and silicate against diatoms is 44.4% and the remaining 55.6% is influenced by other factors.Keyword: The abundance, nitrate, phosphate and silicate, Diatom, Pangkalan Sesai